ISSUES AND PERSPECTIVES OF THE AGROINDUSTRIAL COMPLEX MANUFACTURE DEVELOPMENT IN THE CURRENT CONTEXT OF THE COUNTRY'S ECONOMY MODERNIZATION (EVIDENCE FROM STAVROPOL REGION) - Sergey M. Gorlov; Ovsanna. M. Dgavadova (Вестник Северо-Кавказского федерального университета, 2022)
In article improvement of agroindustrial complex of Stavropol region, problems of development of processing branch of agrarian and industrial complex of Russia and Stavropol region, considerably become aggravated in connection with Russia's accession to the World Trade Organization are designated. The directions of modernization of processing branch of Stavropol region are offered.